FOUNDING THE SENSE FOR MUSICAL FORM IN THE CASE OF PUPILS IN PUBLIC EDUCATION - GYÖRGYJAKAB, Miklós–Csaba (Studia Universitatis Babes-Bolyai Musica, 2010)
Wherever we go, whatever we do nowadays, music is present everywhere. Years ago studies proved that music has an effect on both our environment and our personality. Listening to music is not merely a pastime, a form of entertainment, an element in advertising or a means to capture our attention, but a form of manifestation of the human spirit itself. By music we can express love, joy, happiness, sorrow, inner freedom, quiet revolt, sensational or anything else that is part of the wide scale of feelings.[1] Still, listening to contemporary works of art represents a serious challenge for every individual: the challenge of understanding musical compositions, especially the music of our times. One of the tasks of music teaching is to form a community that would not just be overwhelmed by the unintelligibility of musical pieces, but who is familiar with different musical styles and is able to interpret even unfamiliar musical pieces. It is necessary to develop in children a sense by which they will be able to understand music as a coherent process, instead of regarding it a line or set of dead sounds. Founding the development of such a sense has to start from the earliest of ages when the song performed or sung by the music teacher helps children develop a sense for musical form. In fact, the main and most basic level of a singing performance as far as developing such a sense is concerned is breathing, musical articulation and dynamic shadings. Developing a sense for musical form means enabling pupils to understand the role the parts and elements of the piece of music play in the texture of the piece[2] and to realize how relationships between the various parts of the piece form a coherent unit, i.e. enabling the pupil to follow the logic of the musical process. Developing a sense for musical form has to begin as soon as possible.[3] And has to be continued uninterruptedly, using every suitable musical piece for this purpose.[4] The science of musical form is one of the branches of music, which intends to develop a sense for musical form, which covers all the components of a musical piece and which requires sound knowledge. Therefore the science of musical form is taught only in the graduating classes of music colleges or secondary schools specialized in music. However the pedagogical principle of gradation and continuity requires that pupils should be helped to develop a sense for musical form before being introduced to the science of musical form. Still, the music course books of today deal very little with the practice of the sense for musical form. [1] Gábor, Lajos, A zene hatása a személyiségre (The Effect of the Music on Personality) in Perspektíva, Cluj-Napoca, April 2008. [2] Structural function [3] Even songs consisting of G-E sounds can be formally analysed. [4] Szenik, Ilona, A formaérzék fejlesztésének alapjai (The Basics of Developing Musical Form), In: Zenetudományi írások, ed. Benkő András, Kriterion, Budapest, 1986, 46. (Further on called: Szenik: Musical Form)